2011
DOI: 10.1371/journal.pone.0017762
|View full text |Cite
|
Sign up to set email alerts
|

Robust RT-qPCR Data Normalization: Validation and Selection of Internal Reference Genes during Post-Experimental Data Analysis

Abstract: Reverse transcription and real-time PCR (RT-qPCR) has been widely used for rapid quantification of relative gene expression. To offset technical confounding variations, stably-expressed internal reference genes are measured simultaneously along with target genes for data normalization. Statistic methods have been developed for reference validation; however normalization of RT-qPCR data still remains arbitrary due to pre-experimental determination of particular reference genes. To establish a method for determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
150
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(153 citation statements)
references
References 23 publications
3
150
0
Order By: Relevance
“…For the selected reference genes (α-Tub84b, eif-1a, and CG13220), we next confirmed that the presence plot for each gene matched its corresponding FlyBase model (St Pierre et al 2014). We then selected primers using FlyPrimerBank (Hu et al 2013) and relevant publications (Ling and Salvaterra 2011) and optimized them for qRT-PCR.…”
Section: Reference Genesmentioning
confidence: 61%
See 1 more Smart Citation
“…For the selected reference genes (α-Tub84b, eif-1a, and CG13220), we next confirmed that the presence plot for each gene matched its corresponding FlyBase model (St Pierre et al 2014). We then selected primers using FlyPrimerBank (Hu et al 2013) and relevant publications (Ling and Salvaterra 2011) and optimized them for qRT-PCR.…”
Section: Reference Genesmentioning
confidence: 61%
“…For primer optimization (Eurofins MWG Operon), we produced standard curves using at least five 1:5 dilutions of RNA starting at 50 ng cDNA. Primer sequences were taken from FlyPrimerBank and citations (Ling and Salvaterra 2011;Hu et al 2013). Gene names, primer sequences, amplicon length, efficiency, R 2 of primers are given in Supplemental Table S9.…”
Section: Qrt-pcrmentioning
confidence: 99%
“…For LTR retrotransposons, we designed primers on the basis of the canonical sequence (Supplemental Table 9). To determine the internal controls in qRT-PCR, we followed the protocol in Gan et al (2013) and chose the three most transcriptionally constant genes (eIF-1A, Rap2l, and SdhA) out of 26 in Ling and Salvaterra (2011) and Ponton et al (2011). Strand-specific RNAseq data for line 208 were generated by following the dUTP protocol (Levin et al 2010).…”
Section: Transcriptional Profiling Of Drosophila Polymorphic Retrocopiesmentioning
confidence: 99%
“…Basal levels of neuronal autophagy are believed to decrease with age (Komatsu et al, 2007); however, direct evidence supporting this view is absent. In Drosophila brains autophagy activity during normal aging appears to be stable based on observations that no significant changes occurs in expression levels for several autophagyrelated genes (Ling & Salvaterra, 2011b). Moreover, induction of neuronal autophagy in a conditional Drosophila model is protective in young animals, but likely detrimental in older animals (Ling & Salvaterra, 2011a).…”
Section: Brain Aging and Autophagy-lysosomal Catabolismmentioning
confidence: 99%